ORGANIZATIONAL READINESS OF THE DIRECTORATE OF CYBER INVESTIGATION OF THE METRO JAYA POLICE IN IMPLEMENTING THE SECI MODEL IN HANDLING CYBERCRIME - Sopian Rahmadyanto; Lina Miftahul Jannah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The development of globalization and digital transformation has increased the complexity of cybercrime which demands that law enforcement organizations have adaptive and sustainable knowledge capacity. However, the acceleration of the development of cybercrime modes is often not balanced by the readiness of organizations to manage and transform knowledge as a strategic resource. This study aims to analyze the readiness of the Directorate of Cyber Investigation of the Metro Jaya Police in implementing the SECI Model (Socialization, Externalization, Combination, and Internalization) in handling cybercrime. The research uses a qualitative approach with a literature study method sourced from scientific journals, books, regulations, institutional documents, and various relevant publications that are analyzed descriptively. The results of the study show that the Directorate of Cyber Investigation of the Metro Jaya Police has been ready for every dimension of the SECI Model through the practice of knowledge sharing, documentation of case handling experience, integration of investigative information, and work experience-based learning. However, this readiness still faces challenges in the form of budget limitations, competency gaps and knowledge sharing culture in human resources, and the lack of formal institutionalization of knowledge management policies. This research implies the importance of strengthening policies, human resource capacity building, and sustainable organizational support to build knowledge-based law enforcement organizations that are adaptive to cybercrime dynamics.